Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1177/0142331219867775
|View full text |Cite
|
Sign up to set email alerts
|

Discrete-time backstepping control with nonlinear adaptive disturbance attenuation for the inverted-pendulum system

Abstract: A discrete-time backstepping controller with an active disturbance attenuation property for the Inverted-Pendulum system is constructed in this paper. The main purpose of this study is to show that Immersion and Invariance (I & I) approach can be used to design a nonlinear observer for disturbance estimation and demonstrate its effectiveness considering a nonlinear system with an unstable equilibrium point, namely Inverted-Pendulum system, by utilizing the estimated values in backstepping control design. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…where k 2 is a controller gain. Similarly, considering (36) and (49), equation (43) can be reorganized as…”
Section: Backstepping Controller Design With Coordinate Transformationmentioning
confidence: 99%
See 1 more Smart Citation
“…where k 2 is a controller gain. Similarly, considering (36) and (49), equation (43) can be reorganized as…”
Section: Backstepping Controller Design With Coordinate Transformationmentioning
confidence: 99%
“…35 In the conference paper, 35 we presented a coordinate transformation that enables design of a backstepping controller where the underactuated coordinates are derived to desired operating points but actuated coordinates are assumed to be free, namely, it does not allow to control all the coordinates. On the contrary, in a journal paper, 36 we have mainly addressed the adaptive disturbance attenuation. Nevertheless, we used a special case of the coordinate transform given in Adigu¨zel and Yalc xn 35 to be able to construct a discretetime backstepping controller.…”
Section: Introductionmentioning
confidence: 99%
“…It not only contains the classical “integral action” but also achieves “proportional action,” which is potentially superior to purely integral adaptation based on certainty-equivalence. Therefore, I&I adaptive methodology is applied to various control systems (Adıgüzel and Yalçın, 2021; Gao et al, 2018; Lee and Singh, 2020; Mannarino and Mantegazza, 2014). However, it can only estimate constant parameter or disturbance.…”
Section: Introductionmentioning
confidence: 99%
“…The exiting I&I methodology (Adıgüzel and Yalçın, 2021; Astolfi, 2008; Gao et al, 2018; Lee and Singh, 2020; Mannarino and Mantegazza, 2014) only estimates constant parameter or disturbance. A novel I&I scheme is developed to estimate time-varying disturbances.…”
Section: Introductionmentioning
confidence: 99%
“…A cascade control scheme based on extended state observer (ESO) was developed for an omnidirectional quad-rotor (Lu et al, 2021). Adiguzel and Yalcin (2021) designed a discrete-time backstepping control scheme with an immersion & invariance observer for the inverted-pendulum system. A multi-rate feed-forward control design framework was developed by Zundert et al (2020) to overcome the traditional performance/cost tradeoff, and successful application to an industrial dual-stage wafer system was reported.…”
Section: Introductionmentioning
confidence: 99%